of Applied Mathematics Scientific and Practical Conference Karshi state university 24-25 may, 2024 y. INITIAL-BOUNDARY VALUE PROBLEM ON -DIMENSIONAL TORUS FOR A TIMEFRACTIONAL SUBDIFFUSION EQUATION WITH AN ARBITRARY ELLIPTIC DIFFERENTIAL OPERATOR: of Applied Mathematics Scientific and Practical Conference Karshi state university 24-25 may, 2024 y. INITIAL-BOUNDARY VALUE PROBLEM ON -DIMENSIONAL TORUS FOR A TIMEFRACTIONAL SUBDIFFUSION EQUATION WITH AN ARBITRARY ELLIPTIC DIFFERENTIAL OPERATOR - Ashurov, Ravshan; Mukhiddinova, Oqila (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
An initial-boundary value problem for a time-fractional subdiffusion equation with an arbitrary order elliptic differential operator is considered on -dimensional torus. Uniqueness and existence of the classical solution of the posed problem are proved by the classical Fourier method. Sufficient conditions for the initial function and for the right-hand side of the equation are indicated, under which the corresponding Fourier series converge absolutely and uniformly.